Post-traumatic stress in healthcare workers during the COVID-19 pandemic: a cross-sectional study - Athimni, Z.; Belhadj Chabbeh, N.; Chatti, S.; Chelly, F.; Ben Afia, L.; Bouhoula, M.; Chouchane, A.; Aloui, A.; Kacem, I.; Maoua, M.; Brahem, A.; Kalboussi, H.; et al. (European psychiatry, 2024)
IntroductionDuring the COVID-19 pandemic, healthcare professionals worked under critical care conditions and had to adapt quickly to extreme work situations. They were confronted with several occupational stressors.ObjectivesTo determine the prevalence and factors associated with post-traumatic stress symptoms among healthcare personnel at Farhat Hached Hospital in Sousse during the COVID-19 pandemic.MethodsThis was a descriptive cross-sectional study conducted among care staff at the Farhat Hached University Hospital in Sousse over a 3-month period during the 4th wave of COVID-19. Data were collected using a questionnaire covering socio-professional and medical data. Post-traumatic stress symptoms were assessed using the Impact of Event Scale-Revised (IES-R). Statistical analysis was performed using SPSS.23 software.ResultsOur study included 326 health professionals from the CHU Farhat Hached. The mean age of our population was 36.38 ±10.19 years. The sex ratio was 0.23. Most healthcare staff were married (61.3%) and had dependent children (60.4%). Nurses were the most represented at 32.2%, followed by health technicians (22.7%) and medical residents (18.4%). Average job tenure was 10.62±10.69 years, with extremes ranging from 1 to 39 years. The prevalence of post-traumatic stress disorder was 32.5%. Paramedics were more likely to develop post-traumatic stress symptoms (OR=2.3 (IC95%: 1.4-3.8), p=0.001). Leisure activities were protective factors against post-traumatic stress symptoms (OR=0.4 (IC95%: 0.2-0.8), p=0.018). The multivariate analytical study revealed that being a paramedic and having a personal history of COVID19 infection were independently associated with post-traumatic stress symptoms.ConclusionsOur results demonstrated the significant impact of the COVID-19 pandemic on the mental health of healthcare personnel. Lessons learned from this pandemic should help in the development of context-specific strategies to support healthcare workers and promote the protection of their mental health.Disclosure of InterestNone Declared